High-performance wear-resistant low-precipitation polycarbonate and preparation method thereof

By using modified ABS copolymer and hyperbranched polyester ether in polycarbonate, combined with the compatibility agent KH570, the problem of poor wear resistance of polycarbonate is solved, its wear resistance and impact strength are improved, and its wear resistance and impact strength are reduced. The generation of precipitates achieves better wear resistance and service life.

CN119307082AInactive Publication Date: 2025-01-14ZHEJIANG TONGLI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411847360.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polycarbonate has poor wear resistance and is prone to scratches during friction, affecting its service life and appearance.

Method used

Using modified ABS copolymer and hyperbranched polyester ether, the hyperbranched polyester ether is grafted on the ABS copolymer and introduced double bonds, and the compatibility agent KH570 is added to improve the wear resistance and toughness of the polycarbonate. And the compatibility is enhanced by the mixing of modified ABS copolymer and polycarbonate to form a bridge structure.

Benefits of technology

It significantly improves the wear resistance and impact strength of polycarbonate, reduces wear and scratches, enhances its compatibility with modified ABS copolymers, and reduces the generation of precipitates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 5RDNCT6ALV0AQOZ7XGBWDHCRXS4ERJOEQPQJOOEP
    Figure 5RDNCT6ALV0AQOZ7XGBWDHCRXS4ERJOEQPQJOOEP
  • Figure C7R7KWG9GC7CALF72HENS1XVY4KD0HHPJUGR9JNE
    Figure C7R7KWG9GC7CALF72HENS1XVY4KD0HHPJUGR9JNE
  • Figure RYMDPI3OZCTKUXRIXT4XCFV0KMCTYTYEMUPLEN6Z
    Figure RYMDPI3OZCTKUXRIXT4XCFV0KMCTYTYEMUPLEN6Z
Patent Text Reader

Abstract

The invention relates to the technical field of engineering plastics, and particularly discloses high-performance wear-resistant low-precipitation polycarbonate and a preparation method thereof. The high-performance wear-resistant low-precipitation polycarbonate is prepared from the following raw materials in parts by mass: 80 to 84 parts of polycarbonate, 10 to 20 parts of modified ABS (Acrylonitrile Butadiene Styrene) copolymer, 1 to 5 parts of compatilizer and 0.1 to 0.5 part of antioxidant, the modified ABS copolymer is ABS copolymer grafted hyperbranched polyester ether, and double bonds are introduced into the hyperbranched polyester ether. The high-performance wear-resistant low-precipitation polycarbonate disclosed by the invention has the advantage that the defect that the wear resistance of the polycarbonate is still insufficient can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of engineering plastics, and more specifically, to a high-performance, wear-resistant, low-precipitation polycarbonate and a preparation method thereof. Background Art

[0002] Polycarbonate (Polycarbonate), commonly abbreviated as PC, has the advantages of low density, good toughness, easy processing and low price. It is now the second largest engineering plastic in terms of output after polyamide. Polycarbonate is resistant to weak acids, weak alkalis, neutral oils, heat and impact, and has good mechanical properties within normal use temperatures. Therefore, it is widely used in high-speed rail windows, aviation transparent parts, optical instruments, automobile light strips, construction and other fields.

[0003] However, polycarbonate also has its own disadvantages due to structural problems, such as poor wear resistance. During use, the surface of polycarbonate is often scratched and scratched due to friction, atmospheric dust or surface cleaning, which affects the appearance and thus its service life, limiting its application. Therefore, solving the problem of poor friction resistance of polycarbonate surface has become a hot topic of research. Summary of the invention

[0004] In order to improve the defect that the wear resistance of polycarbonate is still insufficient, the present application provides a high-performance wear-resistant and low-precipitation polycarbonate and a preparation method thereof.

[0005] In the first aspect, the present application provides a high-performance wear-resistant and low-precipitation polycarbonate, which adopts the following technical solution: A high-performance wear-resistant and low-precipitation polycarbonate comprises the following raw materials in parts by weight: 80-84 parts of polycarbonate, 10-20 parts of modified ABS copolymer, 1-5 parts of compatibilizer and 0.1-0.5 parts of antioxidant, wherein the modified ABS copolymer is ABS copolymer grafted with hyperbranched polyester ether, and the hyperbranched polyester ether has double bonds introduced therein.

[0006] Since the molecular chain contains carbonate bonds and aliphatic chain segments, the molecular chain has a certain flexibility and relatively low surface hardness, so it is easy to be scratched during friction, thereby accelerating wear. ABS copolymer is an opaque amorphous thermoplastic engineering plastic with a complex binomial structure. It is composed of three components: styrene, acrylonitrile, and butadiene. The styrene and acrylonitrile components provide a higher surface hardness, which helps to reduce scratches and wear, thereby improving the wear resistance of polycarbonate. Hyperbranched polyester ether is grafted onto the ABS copolymer. Since the hyperbranched polyester ether has a large number of terminal groups and side chains, these functional groups can serve as stress concentration points to effectively absorb and disperse external impact energy. When the ABS copolymer reacts with polycarbonate, the polycarbonate can not only improve the wear resistance but also improve the toughness of the polycarbonate. Double bonds are introduced into the hyperbranched polyester ether, so that the hyperbranched polyester ether can be grafted onto the ABS copolymer.

[0007] Preferably, the compatibilizer is KH570.

[0008] Since the KH570 molecule contains a silane group, this group can react chemically with the hydroxyl group in the hyperbranched polyester ether to form a chemical bond. At the same time, the methacryloyloxy group in KH570 can react with the functional group on the polycarbonate molecular chain to form a bridge between the two materials. The addition of KH570 is beneficial to increase the intermolecular force between polycarbonate and the modified ABS copolymer, so that the polycarbonate and the modified ABS copolymer can be better diffused and mixed when mixed, thereby improving the compatibility between polycarbonate and the modified ABS copolymer, so that the polycarbonate has the characteristics of low precipitates.

[0009] Preferably, the modified ABS copolymer comprises the following raw materials: 45-55 parts of ABS copolymer, 0.3-0.35 parts of hyperbranched polyester ether and 0.13-0.19 parts of initiator.

[0010] Preferably, the preparation method of the modified ABS copolymer is as follows: placing the ABS copolymer in a vacuum drying oven at 80°C-90°C for 10h-14h, weighing 45-55 parts of the dried ABS copolymer, placing it in a heating reaction device at 155°C-165°C and stirring it, then adding 0.13-0.19 parts of initiator and 0.3-0.35 parts of hyperbranched polyester ether and continuing to stir to obtain the modified ABS copolymer.

[0011] Preferably, the ABS copolymer comprises the following raw materials: 35-45 g butadiene latex, 0.1-0.2 g sodium pyrophosphate, 0.1-0.3 g anhydrous glucose, 2.5-3.3 ml ferrous sulfate, 1-3 g sodium oleate, 10-12 g styrene, 3.5-4.1 g acrylonitrile, 0.1-0.14 ml cumene hydroperoxide, 0.1-0.15 ml tert-dodecyl mercaptan, and 0.05-0.13 g antioxidant.

[0012] Preferably, the preparation method of the ABS copolymer is as follows: 35-45g of butadiene latex is weighed and put into a flask for stirring, nitrogen is introduced into the flask, then 0.1-0.2g of sodium pyrophosphate, 0.1-0.3g of anhydrous glucose, 2.5-3.3ml of ferrous sulfate, and 1-3g of sodium oleate are dissolved in 90-100ml of deionized water and added into the flask and stirred at 70-80°C, then 10-12g of styrene, 3.5-4.1g of acrylonitrile mixed monomers are uniformly mixed with 0.1-0.14ml of cumene hydroperoxide and 0.1-0.15ml of tert-dodecyl mercaptan, the mixture is slowly dripped into the flask, reacted for 0.5-1.5h, then 0.05-0.13g of antioxidant is added and stirred for 25-35min, then condensed, dehydrated and dried to obtain an ABS copolymer.

[0013] Preferably, the hyperbranched polyester ether comprises the following raw materials: 1-3 g 3,5-dihydroxybenzoic acid, 4-4.6 g potassium carbonate, 33.56-42.16 ml N,N-dimethylformamide, 3.15-3.19 g 1,6-dibromohexane, 4.9-5.3 g cesium carbonate, and 3-4 g hydroxyethyl acrylate.

[0014] Preferably, the preparation method of the hyperbranched polyester ether is as follows: 1-3g 3,5-dihydroxybenzoic acid, 4-4.6g potassium carbonate and 25.56-26.16ml N,N-dimethylformamide are weighed and added into a flask, stirred at 70-90°C for 8-12min, then 3.15-3.19g 1,6-dibromohexane is quickly added into the flask, reacted for 22-26h, the reaction mixture is cooled to -1-1°C in an ice water bath, 4.9-5.3g cesium carbonate, 3-4g hydroxyethyl acrylate and 8-12ml N,N-dimethylformamide are added, and the reaction is continued at -1-1°C for 22-26h, and after the reaction is completed, filtered and dried.

[0015] Since the main chain and side chains of the hyperbranched polyester ether are usually composed of repeated ester groups and ether groups, these groups are relatively stable chemically and are not easy to form double bonds. Since the present application requires grafting the hyperbranched polyester ether on the ABS copolymer, it is necessary to introduce double bonds into the hyperbranched polyester ether. The molecular structure of hydroxyethyl acrylate contains a hydroxyl group and an acrylate group. The hydroxyl group of hydroxyethyl acrylate can react with the hydrogen atom on the terminal hydroxyl group of the hyperbranched polyester ether, so that the hydroxyethyl acrylate can react with the terminal hydroxyl group of the hyperbranched polyester ether through a chemical reaction to achieve the introduction of double bonds.

[0016] In a second aspect, the present application provides a method for preparing high-performance wear-resistant and low-precipitation polycarbonate, which adopts the following technical solution: A method for preparing high-performance wear-resistant and low-precipitation polycarbonate comprises the following steps: S1: placing polycarbonate and modified ABS copolymer in a vacuum drying oven at 80-100°C and drying for 22-26 hours; S2: Weigh 80-84 parts of dried polycarbonate, 10-20 parts of modified ABS copolymer, 1-5 parts of compatibilizer KH570 and 0.1-0.5 parts of antioxidant, mix well and add into an extruder for extrusion granulation, and dry the obtained particles at 95-105° C. overnight.

[0017] In summary, this application has the following beneficial effects: 1. Because the molecular chain contains carbonate bonds and aliphatic chain segments, the molecular chain has a certain flexibility and relatively low surface hardness, so it is easy to be scratched during friction, thereby accelerating wear. ABS copolymer is an opaque amorphous thermoplastic engineering plastic with a complex binomial structure. It is composed of three components: styrene, acrylonitrile, and butadiene. The styrene and acrylonitrile components provide a higher surface hardness, which helps to reduce scratches and wear, thereby improving the wear resistance of polycarbonate; Hyperbranched polyester ether is grafted onto the ABS copolymer. Since the hyperbranched polyester ether has a large number of terminal groups and side chains, these functional groups can serve as stress concentration points to effectively absorb and disperse external impact energy. When the ABS copolymer reacts with polycarbonate, the polycarbonate can not only improve the wear resistance, but also is not easily affected by the toughness of the polycarbonate. In addition, double bonds are introduced into the hyperbranched polyester ether, so that the hyperbranched polyester ether can be grafted onto the ABS copolymer.

[0018] 2. Since KH570 contains a silane group in the molecule, this group can react chemically with the hydroxyl group in the hyperbranched polyester ether to form a chemical bond. At the same time, the methacryloyloxy group in KH570 can react with the functional group on the polycarbonate molecular chain to form a bridge between the two materials. The addition of KH570 is beneficial to increase the intermolecular force between polycarbonate and the modified ABS copolymer, so that the polycarbonate and the modified ABS copolymer can be better diffused and mixed when mixed, thereby improving the compatibility between polycarbonate and the modified ABS copolymer, so that the polycarbonate has the characteristics of low precipitates.

[0019] 3. Since the main chain and side chains of the hyperbranched polyester ether are usually composed of repeated ester groups and ether groups, these groups are relatively stable chemically and are not easy to form double bonds. Since the present application requires the hyperbranched polyester ether to be grafted onto the ABS copolymer, it is necessary to introduce double bonds into the hyperbranched polyester ether. The molecular structure of hydroxyethyl acrylate contains a hydroxyl group and an acrylate group. The hydroxyl group of hydroxyethyl acrylate can react with the hydrogen atom on the terminal hydroxyl group of the hyperbranched polyester ether, so that hydroxyethyl acrylate can react with the terminal hydroxyl group of the hyperbranched polyester ether through a chemical reaction to achieve the introduction of double bonds. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with Examples 1 to 10 and Comparative Examples 1 to 2.

[0021] Polycarbonate Wanhua Chemical Group Co., Ltd.; Compatibilizer KH570 CAS: 2530-85-0; Antioxidant 1010 CAS: 6683-19-8; Initiator DCP Anhui Xiangyun Rubber & Plastic Co., Ltd.; Butadiene Latex Shandong Yigong Chemical Co., Ltd.; Sodium pyrophosphate CAS: 7722-88-5; Anhydrous glucose CAS: 50-99-7; Ferrous sulfate CAS: 7720-78-7; Sodium oleate CAS: 143-19-1; Styrene CAS: 100-42-5; Acrylonitrile CAS: 107-13-1; Isopropylbenzene hydroperoxide CAS: 80-15-9; Tert-dodecyl mercaptan CAS: 25103-58-6; Antioxidant 1076 Aladdin Reagent (Shanghai) Co., Ltd.; 3,5-Dihydroxybenzoic acid CAS: 99-10-5; Potassium carbonate CAS: 584-08-7; N ,N-Dimethylformamide Bailingwei Technology Co., Ltd.; 1,6-Dibromohexane CAS: 629-03-8; Cesium carbonate CAS: 534-17-8; Hydroxyethyl acrylate CAS: 818-61-1; Magnesium sulfate Sinopharm Chemical Reagent Co., Ltd.; Nitrogen CAS: 7727-37-9; Deionized water CAS: 7732-18-5.

[0022] A high-performance wear-resistant and low-precipitation polycarbonate comprises the following raw materials: 82g of polycarbonate, 15g of modified ABS copolymer, 3g of KH570 and 0.3g of antioxidant 1010.

[0023] Specifically, the preparation method of high-performance wear-resistant and low-precipitation polycarbonate comprises the following steps: S1: Weigh 40g of butadiene latex into a three-necked flask, start the rotor to stir, and introduce nitrogen into the flask to exclude air. Then, dissolve 0.15g of sodium pyrophosphate, 0.2g of anhydrous glucose, 2.9ml of ferrous sulfate, and 2g of sodium oleate in 95ml of deionized water and add them into the three-necked flask and continue stirring at 70-80°C for 10min. Then, mix 11g of styrene and 3.8g of acrylonitrile with 0.12ml of cumene hydroperoxide and 0.13ml of tert-dodecyl mercaptan, and slowly drop the mixture into the three-necked flask to react for 1h. Then, add 0.09g of antioxidant 1010 and stir for 30min, then perform coagulation, dehydrate and dry to obtain ABS copolymer. S2: Weigh 2 g of 3,5-dihydroxybenzoic acid, 4.3 g of potassium carbonate and 25.86 ml of N,N-dimethylformamide into a flask, stir at 80°C for 10 min, then quickly add 3.17 g of 1,6-dibromohexane into the flask and react for 24 h; S3: The reaction mixture was cooled to 0°C in an ice-water bath, 5.1 g of cesium carbonate, 3.5 g of hydroxyethyl acrylate and 10 ml of N,N-dimethylformamide were added, and the reaction was continued at 0°C for 24 h. After the reaction was completed, the mixture was filtered and dried to obtain a hyperbranched polyester ether containing double bonds; S4: drying the ABS copolymer in a vacuum drying oven at 85° C. for 12 h, weighing 50 g of the dried ABS copolymer and placing it in a heating reaction device at 160° C. and stirring it, then adding 0.16 g of initiator DCP and 0.325 g of hyperbranched polyester ether and continuing to stir them to obtain a modified ABS copolymer; S5: placing the polycarbonate and the modified ABS copolymer in a vacuum drying oven at 90° C. and drying for 24 h; S6: 82 g of dried polycarbonate, 15 g of modified ABS copolymer, 3 g of KH570 and 0.3 g of antioxidant 1076 were weighed, mixed evenly and added into an extruder for extrusion granulation. The obtained particles were dried at 100° C. overnight.

[0024] The difference from Example 1 is that the addition amounts of the various components of the high-performance wear-resistant and low-precipitation polycarbonate are different, as shown in Table 1.

[0025] Table 1 Addition amount of each component of high performance wear-resistant low precipitation polycarbonate in Example 1 to Example 3 (g) The difference from Example 1 is that the modified ABS copolymer is replaced by an ABS copolymer with the same addition amount.

[0026] The difference from Example 1 is that the addition amount of each component of the modified ABS copolymer is different, as shown in Table 2.

[0027] Table 2 Addition amount of each component of the modified ABS copolymer in Example 1 and Example 5-Example 6 (g) The difference from Example 1 is that the addition amounts of the components of the ABS copolymer are different, as shown in Table 3.

[0028] Table 3 Addition amount of each component of ABS copolymer in Example 1 and Example 7-Example 8 The difference from Example 1 is that the added amounts of the components of the hyperbranched polyester ether are different, as shown in Table 4.

[0029] Table 4 Addition amount of each component of hyperbranched polyester ether in Example 1 and Example 9-Example 10 The difference from Example 1 is that no modified ABS copolymer is added.

[0030] The difference from Example 1 is that the compatibilizer KH570 is no longer added. 1. Wear resistance test Three samples were taken from Examples 1 to 10 and Comparative Examples 1 to 2, respectively. The samples were injection molded to prepare sheets with a thickness of 3 mm. The surfaces of the sample sheets were evenly wiped with CSI-101 steel wool and then the wear resistance was tested.

[0031] The test data is shown in Table 5.

[0032] Table 5 Wear resistance test table of Example 1-Example 10 and Comparative Example 1-Comparative Example 2 (%) 2. Impact strength test Three samples were taken from Examples 1 to 10 and Comparative Examples 1 to 2, respectively, and the results were compared with those in GB / T 14153-93. "Rigid Plastic Drop Weight Impact Test Method" is used to test the impact strength.

[0033] The test data is shown in Table 6.

[0034] Table 6 Impact strength test table of Example 1-Example 10 and Comparative Example 1-Comparative Example 2 3. Membrane scale quality test Three samples were taken from each of Examples 1 to 10 and Comparative Examples 1 to 2, and the samples were injection molded to prepare square plates of 40×60×2 mm, and the mass of film scale that could be scraped off from the fixed exhaust port was calculated.

[0035] The test data is shown in Table 7.

[0036] Table 7 Membrane scale mass test table of Example 1-Example 10 and Comparative Example 1-Comparative Example 2 (mg) Combining Example 1 and Comparative Example 1 and Tables 5 to 7, it can be seen that, relative to Example 1, the haze before wiping and the haze after wiping of Comparative Example 1 both increase significantly, and there is a large gap between the haze before wiping and the haze after wiping of Comparative Example 1. At the same time, compared with Example 1, the impact strength of Comparative Example 2 decreases significantly, and the film scale quality of Comparative Example 2 increases. This indicates that adding modified ABS copolymers can effectively improve the wear resistance, impact strength and low precipitation of polycarbonate.

[0037] The reason is that ABS copolymer is an opaque, amorphous thermoplastic engineering plastic with a complex binomial structure. It is composed of three components: styrene, acrylonitrile, and butadiene. The styrene and acrylonitrile components provide a higher surface hardness, which helps to reduce scratches and wear, thereby improving the wear resistance of polycarbonate.

[0038] Combining Example 1 and Comparative Example 2 and Tables 5 to 7, it can be seen that, relative to Example 1, the haze before wiping and the haze after wiping of Comparative Example 2 are increased, and there is a large gap between the haze before wiping and the haze after wiping of Comparative Example 2. At the same time, relative to Example 1, the impact strength of Comparative Example 2 is greatly reduced, and the film scale quality of Comparative Example 2 is greatly increased. This shows that the addition of compatibilizer KH570 can effectively improve the wear resistance, impact strength and low precipitation of polycarbonate.

[0039] The reason is that the KH570 molecule contains a silane group, which can react chemically with the hydroxyl group in the hyperbranched polyester ether to form a chemical bond. At the same time, the methacryloyloxy group in KH570 can react with the functional group on the polycarbonate molecular chain to form a bridge between the two materials. The addition of KH570 is beneficial to increase the intermolecular force between polycarbonate and the modified ABS copolymer, so that the polycarbonate and the modified ABS copolymer can be better diffused and mixed when mixed, thereby improving the compatibility between polycarbonate and the modified ABS copolymer, so that the polycarbonate has the characteristics of low precipitates.

[0040] Combining Example 1 and Example 2-Example 3 and Table 5-Table 7, it can be seen that, relative to Example 1, the haze before wiping and the haze after wiping of Example 2-Example 3 are all increased, and the difference between the haze before wiping and the haze after wiping of Example 2-Example 3 is also greater than the difference between the haze before wiping and the haze after wiping of Example 1. At the same time, the impact strength of Example 2-Example 3 is decreased compared with the impact strength of Example 1, and the film scale quality of Example 2-Example 3 is also increased compared with the film scale quality of Example 1. This shows that the addition amount of each component of polycarbonate affects the wear resistance, impact strength and low precipitation of polycarbonate.

[0041] Combining Example 1 and Example 4 and Tables 5 to 7, it can be seen that, relative to Example 1, the haze before wiping and the haze after wiping of Example 4 are both increased, and the difference between the haze before wiping and the haze after wiping of Example 4 is also increased compared to the difference between the haze before wiping and the haze after wiping of Example 1. At the same time, the impact strength of Example 4 is greatly reduced compared to the impact strength of Example 1, and the film scale quality of Example 4 is increased compared to the film scale quality of Example 1. This shows that, compared with adding conventional ABS copolymers, adding modified ABS copolymers can improve the wear resistance, impact strength and low precipitation of polycarbonate.

[0042] The reason is that hyperbranched polyester ether is grafted onto ABS copolymer to obtain modified ABS copolymer. Since hyperbranched polyester ether has a large number of end groups and side chains, these functional groups can serve as stress concentration points to effectively absorb and disperse external impact energy. When the ABS copolymer reacts with polycarbonate, the polycarbonate can not only improve the wear resistance, but also is not easily affected by the toughness of the polycarbonate.

[0043] Combining Example 1 and Example 5-Example 6 and Table 5-Table 7, it can be seen that relative to Example 1, the haze before wiping and the haze after wiping of Example 5-Example 6 are all increased, and the difference between the haze before wiping and the haze after wiping of Example 5-Example 6 is also greater than the difference between the haze before wiping and the haze after wiping of Example 1. At the same time, the impact strength of Example 5-Example 6 is lower than the impact strength of Example 1, and the film scale quality of Example 5-Example 6 is higher than the film scale quality of Example 1. This shows that the addition amount of each component of the modified ABS copolymer affects the wear resistance, impact strength and low precipitation of polycarbonate.

[0044] Combining Example 1 and Example 7-Example 8 and Table 5-Table 7, it can be seen that relative to Example 1, the haze before wiping and the haze after wiping of Example 7-Example 8 are all increased, and the difference between the haze before wiping and the haze after wiping of Example 7-Example 8 is also increased compared with the difference between the haze before wiping and the haze after wiping of Example 1. At the same time, the impact strength of Example 7-Example 8 is decreased compared with the impact strength of Example 1, and the film scale quality of Example 7-Example 8 is increased compared with the film scale quality of Example 1. This shows that the addition amount of each component of the ABS copolymer affects the wear resistance, impact strength and low precipitation of polycarbonate.

[0045] Combining Example 1 and Example 9-Example 10 and Table 5-Table 7, it can be seen that, relative to Example 1, the haze before wiping and the haze after wiping of Example 9-Example 10 are all increased, and the difference between the haze before wiping and the haze after wiping of Example 9-Example 10 is also greater than the difference between the haze before wiping and the haze after wiping of Example 1. At the same time, the impact strength of Example 9-Example 10 is lower than the impact strength of Example 1, and the film scale quality of Example 9-Example 10 is higher than the film scale quality of Example 1. This shows that the addition amount of each component of the hyperbranched polyester ether affects the wear resistance, impact strength and low precipitation of polycarbonate.

[0046] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-performance, wear-resistant, low-precipitation polycarbonate, characterized in that: The invention comprises the following raw materials in parts by weight: 80-84 parts of polycarbonate, 10-20 parts of modified ABS copolymer, 1-5 parts of compatibilizer and 0.1-0.5 parts of antioxidant. The modified ABS copolymer is ABS copolymer grafted with hyperbranched polyester ether, and the hyperbranched polyester ether has double bonds introduced therein.

2. A high-performance, wear-resistant, low-precipitation polycarbonate according to claim 1, characterized in that: The compatibilizer is KH570.

3. A high-performance, wear-resistant, low-precipitation polycarbonate according to claim 2, characterized in that: The modified ABS copolymer comprises the following raw materials: 45-55 parts of ABS copolymer, 0.3-0.35 parts of hyperbranched polyester ether and 0.13-0.19 parts of initiator.

4. The high-performance wear-resistant and low-precipitation polycarbonate according to claim 3, characterized in that: The preparation method of the modified ABS copolymer comprises the following steps: placing the ABS copolymer in a vacuum drying oven at 80° C.-90° C. and drying it for 10 h-14 h, weighing 45-55 parts of the dried ABS copolymer and placing it in a heating reaction device at 155° C.-165° C. and stirring it, then adding 0.13-0.19 parts of an initiator and 0.3-0.35 parts of a hyperbranched polyester ether and continuing to stir it, thereby obtaining the modified ABS copolymer.

5. The high-performance wear-resistant and low-precipitation polycarbonate according to claim 4, characterized in that: The ABS copolymer comprises the following raw materials: 35-45g butadiene latex, 0.1-0.2g sodium pyrophosphate, 0.1-0.3g anhydrous glucose, 2.5-3.3ml ferrous sulfate, 1-3g sodium oleate, 10-12g styrene, 3.5-4.1g acrylonitrile, 0.1-0.14ml cumene hydroperoxide, 0.1-0.15ml tert-dodecyl mercaptan, 0.05-0.13g antioxidant and 90-100ml deionized water.

6. The high-performance wear-resistant and low-precipitation polycarbonate according to claim 5, characterized in that: The preparation method of the ABS copolymer comprises the following steps: weighing 35-45 g of butadiene latex and putting it into a flask for stirring, introducing nitrogen into the flask, then dissolving 0.1-0.2 g of sodium pyrophosphate, 0.1-0.3 g of anhydrous glucose, 2.5-3.3 ml of ferrous sulfate and 1-3 g of sodium oleate in 90-100 ml of deionized water and adding the mixture into the flask for continuous stirring at 70-80° C., then uniformly mixing a mixed monomer of 10-12 g of styrene and 3.5-4.1 g of acrylonitrile with 0.1-0.14 ml of cumene hydroperoxide and 0.1-0.15 ml of tert-dodecyl mercaptan, slowly dropping the mixture into the flask for reaction for 0.5-1.5 h, then adding 0.05-0.13 g of an antioxidant and stirring for 25-35 min, then condensing, dehydrating and drying to obtain the ABS copolymer.

7. A high-performance, wear-resistant, low-precipitation polycarbonate according to claim 6, characterized in that: The hyperbranched polyester ether comprises the following raw materials: 1-3 g 3,5-dihydroxybenzoic acid, 4-4.6 g potassium carbonate, 33.56-42.16 ml N,N-dimethylformamide, 3.15-3.19 g 1,6-dibromohexane, 4.9-5.3 g cesium carbonate, and 3-4 g hydroxyethyl acrylate.

8. The high-performance wear-resistant and low-precipitation polycarbonate according to claim 7, characterized in that: The preparation method of the hyperbranched polyester ether comprises the following steps: weighing 1-3 g of 3,5-dihydroxybenzoic acid, 4-4.6 g of potassium carbonate and 25.56-26.16 ml of N,N-dimethylformamide, adding the mixture into a flask, stirring the mixture at 70-90° C. for 8-12 min, then quickly adding 3.15-3.19 g of 1,6-dibromohexane into the flask, reacting the mixture for 22-26 h, cooling the reaction mixture to -1-1° C. in an ice water bath, adding 4.9-5.3 g of cesium carbonate, 3-4 g of hydroxyethyl acrylate and 8-12 ml of N,N-dimethylformamide, and continuing the reaction at -1-1° C. for 22-26 h, and filtering and drying the mixture after the reaction is completed.

9. The method for preparing a high-performance wear-resistant and low-precipitation polycarbonate according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: placing polycarbonate and modified ABS copolymer in a vacuum drying oven at 80-100°C and drying for 22-26 hours; S2: Weigh 80-84 parts of dried polycarbonate, 10-20 parts of modified ABS copolymer, 1-5 parts of compatibilizer KH570 and 0.1-0.5 parts of antioxidant, mix well and add into an extruder for extrusion granulation, and dry the obtained particles at 95-105° C. overnight.